1999
DOI: 10.1046/j.1369-6513.1999.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer collaboration, patient‐defined outcomes and the preparation of Cochrane Reviews

Abstract: Objectives To identify the extent to which the Cochrane Collaboration involves consumers (patients, carers, patient and non‐patient members of patient/consumer organizations) as members of Cochrane Review Groups (CRGs); to explore the emphasis CRGs place on identifying and collecting information on outcomes identified by patients as being important indicators of quality and effectiveness of treatment and care (‘patient‐defined outcomes’). Method A postal questionnaire designed by The College of Health, a UK pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Given the diversity of perspectives on depression and the implications of these for clinical practice, the development of tools or procedures to identify patients' models of depression and their attitudes towards various management options would be a useful way forward. 44 This study's finding of such a range of differing views on the desired outcome of managing depression also has implications for the outcomes assessed in clinical trials, 45 and for GPs' implementation of evidence-based medicine, since the evidence base may not address outcomes salient to all patients. Research methods as well as guidelines need to show greater awareness of the varied perspectives about depression.…”
Section: Implications For Future Research or Clinical Practicementioning
confidence: 98%
“…Given the diversity of perspectives on depression and the implications of these for clinical practice, the development of tools or procedures to identify patients' models of depression and their attitudes towards various management options would be a useful way forward. 44 This study's finding of such a range of differing views on the desired outcome of managing depression also has implications for the outcomes assessed in clinical trials, 45 and for GPs' implementation of evidence-based medicine, since the evidence base may not address outcomes salient to all patients. Research methods as well as guidelines need to show greater awareness of the varied perspectives about depression.…”
Section: Implications For Future Research or Clinical Practicementioning
confidence: 98%
“…These principles encapsulate consumer involvement and we found several reports of consumer involvement in the Cochrane Collaboration. Cochrane Review Groups are collaborations between consumers and professionals which are often less formal than committee membership, [28][29][30][31] perhaps necessarily in view of their international nature. Teamworking may be a more appropriate descriptor.…”
Section: A3 International Collaborationsmentioning
confidence: 99%
“…31 The emphasis on 'patientdefined' outcomes rather than 'patient-centred' outcomes invoked consumer involvement in setting research agendas. The survey found that four Review Groups had made some headway involving consumers through a variety of mechanisms.…”
Section: A3 International Collaborationsmentioning
confidence: 99%
See 1 more Smart Citation
“…293,294 Patient-based outcome measures can contribute to the evaluation of the quality of health care and the performance of health professionals 295 play a role in consumer involvement in the wider health services research agenda. 296 Generic instruments for measuring patient-based outcomes can be divided into those that are not preference-based (quality of life, health profiles or health status measures) and preference-based measures (including utilities).…”
Section: Patient-based Outcome Measures For Childrenmentioning
confidence: 99%